Reactivity of Ce-ZrO2 (doped with La-, Gd-, Nb-, and Sm-) toward partial oxidation of liquefied petroleum gas: Its application for sequential partial oxidation/steam reforming - N. Laosiripojana (2018)
Ce-ZrO2 was found to have useful partial oxidation activity under moderate temperatures. It converted liquefied petroleum gas (LPG) to H2, CH4, CO and CO2 with small amounts of C2H6 and C2H4 formations depending on the operating temperature and provided significantly greater resistance toward carbon deposition compared to conventional Ni/Al2O 3. The doping of La, Sm and Gd over Ce-ZrO2 considerably improved catalytic reactivity, whereas Nb-doping reduced its reactivity. It was found that the impact of doping element is strongly related to the degrees of oxygen storage capacity (OSC) and/or lattice oxygen (OOx) of materials. Among all catalysts, La-doped Ce-ZrO2 was observed to have highest OSC value and was the most active catalyst. Above 850 °C with inlet LPG/O2 molar ratio of 1.0/1.0, the main products from the reaction over La-doped Ce-ZrO2 were H2, CH4, CO, and CO2. Practical application was then proposed by applying La-doped Ce-ZrO2 as primary oxidative catalyst for sequential partial oxidation/steam reforming of LPG (by using Ni/Al2O3 as the steam reforming catalyst). At 850 °C, this coupling pattern offered high H2 yield (87.0-91.4%) without any hydrocarbons left in the products indicating the complete conversion of LPG to syngas. H2 yield from this system was almost identical to that observed from the typical autothermal reforming over Rh/Al2O3; hence it could efficiently replace the requirement of expensive noble metal catalysts to reform LPG properly. © 2010 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.